The tiger rising - DiCamillo, Kate (Somerville, Massachusetts : Candlewick Press, 2006)
Rob, who passes the time in his rural Florida community by wood carving, is drawn by his spunky but angry friend Sistine into a plan to free a caged tiger.
Keywords: Tiger -- Fiction; Animal welfare -- Fiction; Animal fiction